2021
DOI: 10.3390/molecules26133946
|View full text |Cite
|
Sign up to set email alerts
|

Double-Chain Cationic Surfactants: Swelling, Structure, Phase Transitions and Additive Effects

Abstract: Double-chain amphiphilic compounds, including surfactants and lipids, have broad significance in applications like personal care and biology. A study on the phase structures and their transitions focusing on dioctadecyldimethylammonium chloride (DODAC), used inter alia in hair conditioners, is presented. The phase behaviour is dominated by two bilayer lamellar phases, Lβ and Lα, with “solid” and “melted” alkyl chains, respectively. In particular, the study is focused on the effect of additives of different pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…No such post-transition is observed in the present study (70 mM). While comparing the main phase transition temperature (T m ) and associated enthalpy ( H), it is found that DODAB membrane has relatively higher T m and associated H compared to DHDAB [74]. This is consistent with the trend observed for natural phospholipid membranes such as phosphocholine lipid membrane where T m and associated H increase with chain length.…”
Section: B Phase Behavior Of Dhdab Membranesupporting
confidence: 82%
“…No such post-transition is observed in the present study (70 mM). While comparing the main phase transition temperature (T m ) and associated enthalpy ( H), it is found that DODAB membrane has relatively higher T m and associated H compared to DHDAB [74]. This is consistent with the trend observed for natural phospholipid membranes such as phosphocholine lipid membrane where T m and associated H increase with chain length.…”
Section: B Phase Behavior Of Dhdab Membranesupporting
confidence: 82%
“…Hair conditioner formulations were developed based on the available published data [5,[23][24][25][26][27][28][29][30][31][32] with slight modifications. A total of seven emulsions were prepared, containing different plant powders at varying concentrations.…”
Section: Formulationsmentioning
confidence: 99%